Mengembangkan Lingkungan Sekolah yang Bebas Bullying Melalui Pembelajaran PPKN - Salsabila Aljannah; Asep Deni Normansyah; Cep Miftah Khoerudin (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research seeks to find out what causes juvenile delinquency at SMP SUMATRA 40 Bandung. The method used in this research is qualitative. This research is motivated by the phenomenon of students experiencing bullying and the impact or influence of these actions in the student's social sphere. This research aims to reveal the level of bullying and the influence of bullying through learning about Pancasila and citizenship education in class VIII at SMP SUMATRA 40 Bandung. Bullying is an experience that can be experienced by some children at school in the form of physical, verbal or psychological threats such as taunting, mocking, hitting or threatening a student victim by several students. The results of the research show that the role of PPKn teachers in preventing bullying behavior through learning Pancasila and citizenship education still cannot be optimized because there are students who are physically small, weak, students who lack self-confidence, have difficulty adjusting to the environment and are considered unattractive in the environment. school.